A precision medicine test predicts clinical response after idarubicin and cytarabine induction therapy in AML patients. (January 2019) - Martínez-Cuadrón, David; Gil, Cristina; Serrano, Josefina; Rodríguez, Gabriela; Pérez-Oteyza, Jaime; García-Boyero, Raimundo; Jiménez-Bravo, Santiago; Vives, Susana; Vidriales, María Belén; Lavilla, Esperanza; Pérez-Simón, José A.; Tormo, Mar; et al.
Highlights: Ex vivo test predicts the response to first line CYT and IDA induction chemotherapy. The use of whole bone marrow samples could lead to more reliable results. Automated flow cytometry reduces experimental errors and provides accurate data. The statistical model used has predictive ability for IDA/CYT patient response. Cytogenetic risk is less predictive than the pharmacologic parameters. Abstract: Complete remission (CR) after induction therapy is the first treatment goal in acute myeloid leukemia (AML) patients and has prognostic impact. Our purpose is to determine the correlation between the observed CR/CRi rate after idarubicin (IDA) and cytarabine (CYT) 3 + 7 induction and the leukemic chemosensitivity measured by an ex vivo test of drug activity. Bone marrow samples from adult patients with newly diagnosed AML were included in this study. Whole bone marrow samples were incubated for 48 h in well plates containing IDA, CYT, or their combination. Pharmacological response parameters were estimated using population pharmacodynamic models. Patients attaining a CR/CRi with up to two induction cycles of 3 + 7 were classified as responders and the remaining as resistant. A total of 123 patients fulfilled the inclusion criteria and were evaluable for correlation analyses. The strongest clinical predictors were the area under the curve of the concentration response curves of CYT and IDA. The overall accuracy achieved using MaxSpSe criteria to define positivity was 81%, predicting better responder (93%) than non-responder patients (60%). The ex vivo test provides better yet similar information than cytogenetics, but can be provided before treatment representing a valuable in-time addition. After validation in an external cohort, this novel ex vivo test could be useful to select AML patients for 3 + 7 regimen vs. alternative schedules.